EFEKTIVITAS PENGELOLAAN KELAS DALAM PEMBELAJARAN PADA TATAP MUKA DIKLAT - Ni Made Riani; Ni Putu Nyoman Nurani (STIMI Handayani Denpasar, 2019)
Realizing quality learning must begin with the consistent attitude of the widyaiswara in preparing the program and in carrying out the learning process. In essence the process of education and training is the process of communication. Teaching and learning activities in the classroom is a separate world of communication where widyaiswara and training participants exchange ideas to develop ideas and understanding. In communication there are frequent irregularities so that communication is not effective. Therefore, so that the education and training process can run effectively, the widyaiswara must be able to manage learning in the classroom professionally. The purpose of writing is to increase the consistency of widyaiswara in preparing the program and the learning process in each activity. The method used is descriptive analysis and is a combination of library/document research with field research. The results of the study show that the consistency of the implementation of a conducive learning climate through optimal classroom management is absolutely necessary so that the effectiveness of learning can be realized and the dominance of learning activities is in the training participants.